Optically Integrated InP–Si$_3$ N$_4$ Hybrid Laser - Youwen Fan; Jorn P. Epping; Ruud M. Oldenbeuving; Chris G. H. Roeloffzen; Marcel Hoekman; Ronald Dekker; Rene G. Heideman; Peter J. M. van der Slot; Klaus-J. Boller (IEEE Photonics Journal)
We describe the first demonstration and characterization of an optically integrated InP–Si $_3$ N $_4$ hybrid laser. The laser is formed by integration of an InP-based reflective semiconductor optical amplifier with a Si $_3$ N $_4$ based feedback waveguide circuit. The circuit comprises a frequency selective and tunable Vernier mirror composed of two microring resonators with slightly different radii. A wide tuning range of more than 43 nm is achieved via the thermo-optic effect. The typical side mode suppression ratio is 35 dB. The narrowest linewidth achieved is about 90 kHz, and the relative intensity noise is less than $-$ 135 dBc/Hz.